The Settlement Patterns in Roshtkhar Plain, Northeastern of Iran. Issue 2 (3rd July 2019) - Rezaei, Mohammad Hossein; Ebrahimi, Javad Zanganeh; Basafa, Hassan
ABSTRACT: Understanding the interaction of human communities and their ecosystem is one of the major goals of archaeological field studies. The climate, unique geographical location, and strategic position of Roshtkhar along the natural corridor between northeastern Iran and Central Asia have attracted the interest of people for some time. The geographical location of Roshtkhar clearly demonstrates the importance of this area, and the need for archaeological studies of north-eastern Iran. In particular, it justifies the importance of undertaking regional archeological research. In order to record the position and shape of topographic features in Roshtkhar, an archaeological field study was carried out, and random sampling of surface findings. In the archaeological exploration of this area, 16 sites belonging to the prehistoric period were identified. The oldest period of settlement dates back to the late Chalcolithic period, but these findings are not definitive, as natural factors such as erosion and sedimentation, along with human factors and potential damage may have affected this area. In this paper, the settlement pattern of Roshtkhar was analysed based upon archaeological studies, and dating of historical sites based upon surface data. Finally, the role of the ecosystem in the formation of Roshtkhar plains was assessed using ArcGIS software.